2013
DOI: 10.2174/18715281113129990054
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvement in ANCA (+) and ANCA (-) Churg-Strauss Syndrome Evaluated by Cardiovascular Magnetic Resonance

Abstract: Cardiac involvement either as DSF or myocarditis, can be detected in both ANCA (+) and ANCA (-) CSS, although more clinically overt in ANCA (-). DSF carries an ominous prognosis for LV function. CMR, due to its capability to detect disease severity, before cardiac dysfunction takes place, is an excellent tool for CSS risk stratification and treatment individualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Moreover, previous cross-sectional studies predominantly used ECG and/or echocardiography only [5][6][7][8][10][11][12][13], whereas studies using cardiac magnetic resonance imaging (CMR) and invasive methods are scarce and the number of patients included low [9,14,15]. To date, two longitudinal studies suggested myocardial fibrosis was associated with adverse outcome in EGPA patients, but the small and descriptive nature prohibits any definitive conclusions [14,18]. Thus, there is lack of prospective studies with contemporary noninvasive and invasive imaging to define the true prevalence of cardiac involvement in EGPA and GPA and link this involvement to long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous cross-sectional studies predominantly used ECG and/or echocardiography only [5][6][7][8][10][11][12][13], whereas studies using cardiac magnetic resonance imaging (CMR) and invasive methods are scarce and the number of patients included low [9,14,15]. To date, two longitudinal studies suggested myocardial fibrosis was associated with adverse outcome in EGPA patients, but the small and descriptive nature prohibits any definitive conclusions [14,18]. Thus, there is lack of prospective studies with contemporary noninvasive and invasive imaging to define the true prevalence of cardiac involvement in EGPA and GPA and link this involvement to long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of EGPA itself has varying challenges, one of which is the fact that a patient with cardiac involvement may present with anti-neutrophil cytoplasmic antibody (ANCA) positivity less frequently than a patient without cardiac involvement [16]. The current use of ECG for the detection of cardiovascular involvement is limited to evaluating left ventricular (LV) wall motion and functional changes [20]. The shortcomings of ECG include the inability to identify tissue damage and the detection of other types of damage before there are apparent LV abnormalities [20].…”
Section: Cmr Use In Diagnosticsmentioning
confidence: 99%
“…The current use of ECG for the detection of cardiovascular involvement is limited to evaluating left ventricular (LV) wall motion and functional changes [20]. The shortcomings of ECG include the inability to identify tissue damage and the detection of other types of damage before there are apparent LV abnormalities [20]. The absence of chest pain and ECG abnormalities can lead to a false sense of security, even in patients with increased troponin levels.…”
Section: Cmr Use In Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of fibrotic tissue, as assessed by LGE, is an independent predictor for future cardiac events [35].…”
Section: Coronary Artery Disease With Ischemic Type Fibrosismentioning
confidence: 99%